The LABELING AND PACKAGING AS A MARKETING STRATEGY FOR UMKM IN GALENGDOWO VILLAGE, WONOSALAM DISTRICT - Maulidia , Ayu; Zawawi , Zawawi (Universitas Negeri Surabaya, 2025)
This research discusses the role of labeling and packaging as a marketing strategy for micro, small and medium enterprises (MSMEs) in Galengdowo village, Wonosalam district. The main focus of this research is to understand how implementing effective labels and packaging can increase the competitiveness of MSME products in regional markets. This study also identifies the obstacles faced by MSMEs in implementing labeling and packaging strategies and finds solutions to overcome these obstacles. With provides a detailed analysis of the factors that influence the choice of design, materials and messages on labels and packaging. It is hoped that this research can provide practical and applicable recommendations for MSMEs. The research results show that label and packaging innovation has the potential to expand market share, increase competitiveness, strengthen the brand image of MSME products, and ultimately support regional economic growth. Keywords: MSME, packaging, labeling, marketing, innovation